EP891 Receptor activator of nuclear factor kappa-B ligand expression predicts ovarian cancer outcome. (1st November 2019) - Kögl, J; Wieser, V; Sprung, S; Fiegl, H; Marth, C; Zeimet, AG
Abstract : Introduction/Background: The receptor activator of nuclear factor-κB (RANK) pathway, activated by RANK ligand (RANKL), critically controls bone metabolism and modulates tumour immune response. Denosumab, a neutralizing RANKL antibody, exerts tumour-suppressive effects in mice and humans. Herein, the relevance of RANK signalling was investigated for the first time in human ovarian cancer (OC). Methodology: RANK, RANKL and OPG expression of 192 epithelial OCs and 12 non-malignant fallopian tubes was related to clinico-pathological characteristics. Regulation of RANK constituents was studied in four OC cell lines and the impact of RANK ligation or denosumab treatment on cell viability was determined. Results: In OC, RANK constituents (RANK, RANKL and OPG) were expressed in epithelial and stromal cells. RANKL (but not RANK ) expression was elevated in OC tissue, particularly in BRCA1/2 mutated tumours and correlated with BRCA2 expression. RANKL expression independently predicted progression free and overall survival. Expression of RANK constituents in OC cells was induced by inflammatory cytokines such as IL-1β and TNFα. However, neither RANK ligation nor denosumab treatment influenced OC cell viability. Conclusion: This study links RANKL expression independently to patient's outcome in OC and implicates RANK signalling in the pathogenesis and the inflammatory response of OC. Denosumab may prove efficacious in OC. Disclosure: Nothing to disclose.